The Individuation process of the main character in Husein Mahran’s Sanawat Ats-Tsaqb Al-Aswad: A Jungian perspective - Arina Zakiah Azzahra; Arif Mustofa (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
The conflict between the inner world and the need to find identity is a common topic discussed in contemporary literature, particularly through symbols of psychological relationships. However, a significant number of Jungian literary interpretations continue to view archetypes as fixed symbols, rather than as interconnected processes of individualization. This gap can be traced in readings of contemporary Arabic novels, such as Husein Mahran's Sanawat Ats-Tsaqb Al-Aswad, which depicts the main character, Yasin Imran, as torn between social norms and his strong inner desires. This paper will examine how Jungian archetypes are reflected and how the interaction between them contributes to the main character's individualization process. This paper is a combination of descriptive qualitative research and literary psychology based on Carl Gustav Jung's theory of archetypes. The primary data source is the 2021 edition of Sanawat Ats-Tsaqb Al-Aswad, and the secondary data are based on relevant academic literature on analytical psychology and literary works. Data collection involved a careful reading of narrative passages, conversations, and descriptions that exhibit characteristics of Jungian archetypes. The data were analyzed using Miles and Huberman's interactive approach, which includes data reduction, data display, and conclusion drawing. The results of this study indicate that the four Jungian archetypes presented in the novel represent evolutionary stages in Yasin's psychological growth. Yasin's persona is shown as a disciplined and obedient character, a mask used socially to maintain social stability. The shadow is Yasin's duplicate and depicts an unrealized life, emphasizing the dissociation between ego and inner desires. The anima manifests through Yasin's emotional involvement with Farida, thus intensifying the conflict between rationality and affectivity. Ultimately, the conflict between the two versions of Yasin's personality reflects the archetype of the self, meaning the union of the ego with all parts of the soul. Conceptually, through this study, the concept of archetype can be applied in contemporary Arabic literature not only as a psychological symbol but also as a narrative structure that shapes the individualization of the protagonist.